Forming Human Excellence on Education through 4Cs Characters: A Literature Study - Pradita, Adventia Putri (Spiritualitas Ignasian: Jurnal Kerohanian dalam Dunia Pendidikan, 2023)
The word "excellence" which comes from the Latin word "excellentia," meaning quality of being extremely good. According to Deretic (2011), human excellence can be defined as the qualities of a person that make them outstand in human activities or can also be referred to as moral excellence. Without human excellence, future science and ethics will have a difficult task in evaluating such excellence correctly. Jesuit schools have one of their goals in education to form human excellence for their students. Father Arrupe, SJ stated that human excellence to be achieved by students is to become men and women for and with others. This is then supported by Father Kolvenbach, SJ's opinion that men and women for and with others are people who have the 4C character, namely competence, compassion, conscience, and commitment. This work will study the formation of human excellence with the 4Cs aspect in education. The methodology used in this work is a systematic literature review. This research collects information from books, book sections, journal articles, conference reports, and conference proceedings. The search keywords for this study are human excellence, competence, compassion, conscience, commitment, Jesuit education, Ignatius Loyola, Ignatian pedagogy paradigm, educate magis, and Spiritual Exercises. The result of this work is Jesuit education forms human excellence through 4Cs character. The 4Cs characters in education forms human excellence by developing the whole or complete abilities of an individual, not only for themselves but also for others, as a holistic person, and by forming a deep relationship with God as the creator. Especially, Ignatian Pedagogy Paradigm could form 4Cs character through context, experience, reflection, action, and evaluation steps.